High‐resolution short‐T2 MRI using a high‐performance gradient. Issue 4 (16th March 2020) - Froidevaux, Romain; Weiger, Markus; Rösler, Manuela B.; Brunner, David O.; Dietrich, Benjamin E.; Reber, Jonas; Pruessmann, Klaas P.
Abstract : Purpose: To achieve high resolution in imaging of short‐T2 materials and tissues by using a high‐performance human‐sized gradient insert with strength up to 200 mT/m and 100% duty cycle. Methods: Dedicated short‐T2 methodology and hardware are used, such as the pointwise encoding time reduction with radial acquisition (PETRA) technique with modulated excitation pulses, optimized radio‐frequency hardware, and a high‐performance gradient insert. A theoretical analysis of actual spatial resolution and SNR is provided to support the choice of scan parameters and interpretation of the results. Imaging is performed in resolution phantoms, animal specimen, and human volunteers at both conventional and maximum available gradient strengths and compared using image subtraction. Results: Calculations suggest that increasing gradient strength beyond conventional values considerably improves both actual resolution and SNR efficiency in short‐T2 imaging. Resolution improvements are confirmed in all investigated samples, in particular 2 mm slots were resolved in a hard‐plastic plate with T 2 ≈ 10 μs and in vivo musculoskeletal images were acquired at isotropic 200 μm resolution. Expected improvements in signal yield are realized in fine structures benefitting from high resolution but to less extent in regions of low contrast where decay‐related blurring leads to signal overlap between neighboring locations. Conclusion: Strong gradients with high duty cycle enable short‐T2 imaging at unprecedentedly high resolution, holding the potential for improving MRI of, eg, bone, tendon, lung, or teeth. Moreover, it allows direct access of tissues with T 2 of tens of microseconds such as myelin or collagen.